MIKROPROPAGASI DUKU (Lancium domesticum L., cv. Kalikajar) MELALUI KULTUR PUCUK - Aman Suyadi (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2009)
The objectives of the research are to find out the influence of the mix between Kinetin and NAA and their best concentration level to result in the best effect on micropropagation of duku through shoot tip culture and to getting identic seedling of duku. The research was conducted in February to November 2007. It used randomized completely block design to constitute a three-repeated treatment. The treatment is made up by two factors. The first factor is the concentration of Kinetin consisting of three levels, those are 0 M (K0), 10-7 M (K7), and 10-6 M (K6). The second factor is the concentration of NAA, consisting of four levels, they are 0 M (N0), 10-7 M (N7), 10-6 M (N6) and 10-5 M (B5). The result of the study shows that the concentration combination of Kinetin and NAA has an influence to the shoot induction, this is number of shoots per eksplant, shoot multiplication I, those are number of leaves, shoot multiplication II, those are number of shoots per eksplant, number of leaves, buds length, shoot multiplication III, this is buds length, and root induction, those are number of roots and roots length. The best concentration combinations of Kinetin and NAA for shoot induction, shoot multiplication are K6N5, for root induction is K0N5. Those concentration combination respectively produce 3.05 shoots, 3.65 shoots, and 3,6 roots. Key words : kinetin, NAA, shoot tip, multiplication